Isomer‐Pure Bis‐PCBM‐Assisted Crystal Engineering of Perovskite Solar Cells Showing Excellent Efficiency and Stability. Issue 17 (27th February 2017) - Zhang, Fei; Shi, Wenda; Luo, Jingshan; Pellet, Norman; Yi, Chenyi; Li, Xiong; Zhao, Xiaoming; Dennis, T. John S.; Li, Xianggao; Wang, Shirong; Xiao, Yin; Zakeeruddin, Shaik Mohammed; et al.
Abstract : A fullerene derivative (α‐bis‐PCBM) is purified from an as‐produced bis‐phenyl‐C61 ‐butyric acid methyl ester (bis‐[60]PCBM) isomer mixture by preparative peak‐recycling, high‐performance liquid chromatography, and is employed as a templating agent for solution processing of metal halide perovskite films via an antisolvent method. The resulting α‐bis‐PCBM‐containing perovskite solar cells achieve better stability, efficiency, and reproducibility when compared with analogous cells containing PCBM. α‐bis‐PCBM fills the vacancies and grain boundaries of the perovskite film, enhancing the crystallization of perovskites and addressing the issue of slow electron extraction. In addition, α‐bis‐PCBM resists the ingression of moisture and passivates voids or pinholes generated in the hole‐transporting layer. As a result, a power conversion efficiency (PCE) of 20.8% is obtained, compared with 19.9% by PCBM, and is accompanied by excellent stability under heat and simulated sunlight. The PCE of unsealed devices dropped by less than 10% in ambient air (40% RH) after 44 d at 65 °C, and by 4% after 600 h under continuous full‐sun illumination and maximum power point tracking, respectively. Abstract : Significantly improved performance of mixed perovskite solar cells, using a facile α‐bis‐PCBM‐containing perovskite growth method during device fabrication, is reported. The newly developed perovskite solar cell exhibits an enhanced power conversion efficiency of 20.8%, along with enhanced stability under heat and illumination.